Effect of Sleep Quality in Amyloid Plague Accumulation in Alzheimers (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
This study examined the effect of sleep quality in amyloid plague accumulation in alzheimers disease. The study mentioned that Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by cognitive decline, memory impairment, and the accumulation of amyloid-beta (Aβ) plaques in the brain. In carrying out this research, the following subheads were explored: concept of sleep, concept of sleep quality, concept of amyliod plague accumulation and concept of alzheimer’s disease. The need for sleep quality as mentioned in the study included: for improved mood, for healthy heart and to regulated blood sugar. Similarly, the study mentioned the effects of sleep quality in amyloid plague accumulation in Alzheimer to include: impaired glymphatic clearance of amyloid-beta, increased tau protein accumulation and APOE-ε4 /sleep disruptions in alzheimer's risk. Furthermore, the study mentioned cognitive behavioral therapy for insomnia (CBT-I), melatonin supplementation and physical activity/ exercise how to improve sleep quality. The study concluded that emerging evidence highlights the crucial role of sleep quality in regulating amyloid-beta accumulation and the progression of Alzheimer’s disease. One of the recommendations made was that public health initiatives should raise awareness about the importance of sleep in brain health.